Pengaruh Kualitas Produk, Persepsi Harga Dan Lokasi Terhadap Keputusan Pembelian (Studi Kasus Rocket Chicken Cabang Kabupaten Kendal) - Ivana Khoiru Amalia; Ali Maskur (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
This study aims to analyze the effect of product quality, perceived price and location on purchasing decisions. The object of research is Rocket Chicken Kendal Regency Branch and the independent variables in the study are product quality, price perception and location, then the dependent variable is purchasing decisions. The population in this study were customers who bought the product at least once at Rocket Chicken, Kendal Regency, the researchers took a sample of 100 respondents. The sampling technique in this study used purposive sampling, namely the technique of determining the sample with certain criteria. The data used in this study is primary data, using a questionnaire as a research instrument. The analytical tools used are validity test, reliability test, F test, coefficient of determination (R²) test, multiple linear regression and t test Versi spss 16.The results showed that product quality had a positive and significant effect on purchasing decisions, price perceptions had a positive and insignificant effect on purchasing decisions, location had a positive and significant effect on purchasing decisions.